THE MAIN TASKS OF THE FORMATION OF PROFESSIONAL QUALITIES IN FUTURE EDUCATORS (Academia Science Repository, 2023)
When organizing a pedagogical process aimed at ensuring the professional development of future pedagogical educators, it is necessary to study the existing knowledge, professional inclinations, needs of students. Educators during their activities should be able to create a healthy environment among colleagues and the children's community, to gain a reputation in the community. This article will provide feedback and feedback on the main tasks of the formation of professional qualities in future educators.